GENETIC ALGORITM ECLIPSE MAPPING - Halevin, A. V. (Одеські астрономічні публікації, 2007)
In this paper we analyse capabilities of eclipse mapping technique, based on genetic algorithm optimization. To model of accretion disk we used the "fire-flies" conception. This model allows us to reconstruct the distribution of radiating medium in the disk using less number of free parameters than in other methods. Test models show that we can achieve good approximation without optimizing techniques.